The Prevalence and Outcomes of Thrombocytopenia in a Neonatal Intensive Care Unit: A Three-Year Report - İÇAĞASIOĞLU, DİLARA FÜSUN; BOLAT, FATİH; Kilic, Suar Caki; OFLAZ, MEHMET BURHAN; GULHAN, Elif; KAYA, Ali; GÜVEN, AHMET SAMİ; AYGUNES, Utku; Icagasioglu, Dilara; GÜLTEKİN, ASIM (My University, 2012)
Neonatal thrombocytopenia is one of the most common hematologic disorders in neonatal intensive care units (NICUs). The purpose of this study was to determine the prevalence of thrombocytopenia and whether thrombocytopenia has an effect on the occurrence of intraventricular hemorrhage (IVH) >= grade 2 and on mortality rate. This study was carried out retrospectively in neonates admitted to NICU of Cumhuriyet University in Sivas, Turkey, between 2009 and 2012. Among 2218 neonates evaluated, 208 (9.4%) developed thrombocytopenia. The prevalence of IVH >= grade 2 was more in infants with thrombocytopenia (7.2%) than in those without thrombocytopenia (4.4%), although this was not statistically significant (P=.08). In univariate analysis, IVH >= grade 2 was higher in cases with very severe thrombocytopenia (35.7%, n = 5) than in those with mild (2.1%, n = 2), moderate (4.7%, n = 3), and severe thrombocytopenia (15.2%, n = 5) (P=.04). Multivariate logistic regression analysis showed that birth weight = 2 (OR 7.3, 95% CI 4.1-12.1; P=.001) were significant risk factors for mortality. The results of our study suggest that outcomes of neonates with thrombocytopenia depend not only on platelet count but also on decreased gestational age or birth weight, prenatal factors, and sepsis.